Praktik Mediasi Sebagai Alternatif Penyelesaian Sengketa Batas di Kantor Pertanahan Kota Kediri - Firda Adita Nurul Ihsani; Grahadi Purna Putra (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
In the current era, land is a basic need that is extremely important and meaningful in human life, particularly as a place to live, work, farm, or conduct various economic activities. With the rapidly growing population, the demand for residential land is also increasing. The population growth that is not matched by land availability creates significant pressure in the property market, leading to the development of new housing and settlements, both in urban and suburban areas. However, due to the increasingly limited availability of habitable land, this often triggers intense competition among individuals or parties with vested interests in obtaining land rights. The desire to own land has become very strong, as nowadays, land is not only used as a residence but also as a valuable resource. This often causes land disputes where the parties involved feel disadvantaged, either due to overlapping ownership, unclear land status claims, or differences in land use allocation. Due to the increasingly complex issues, the Land Office of Kediri City provides an alternative solution for boundary dispute resolution, namely mediation. This practice is an effort to resolve land conflicts peacefully and efficiently. Land disputes are becoming more complex and prolonged, often involving the government, businesses, and local residents. Moreover, land-related issues are frequently associated with unclear administration, weak law enforcement, or differing interpretations of existing regulations. As a result, not only does it impact the individuals involved, but it can also affect social and economic stability in a region. To address these issues, a more structured and transparent approach to land distribution and management is required. The government and society must work together to ensure fair and clear land distribution and provide wise solutions to disputes based on the principles of social justice. Mediation offers a more flexible approach compared to litigation by prioritizing dialogue among disputing parties. In this context, mediation helps alleviate tensions and create mutually beneficial solutions, enabling faster and more cost-effective processes. This study analyzes the effectiveness of mediation practices in reducing the number of disputes brought to court and assesses public perceptions of this resolution method. The results show that mediation can increase the satisfaction of the parties involved and promote stability in land ownership.